Proclivity For Religiosity In The Styles And Motifs Of The Arabic Writings Of Yoruba ‘ulamā’ - Mikail Adebisi Folorunsho (The Journal of Studies in Language, Culture and Society, 2024)
Of the notable features of the Arabic writings of the Arabic literati of Yoruba extraction is their propensity for religiosity. A closer examination of the Arabic writings of Yoruba ‘Ulamā’ (scholars) reveals the influence of Islam on the style as well as the themes of their literary productions. Arabic works of these scholars exhibit a strong predilection and preference for styles that are embedded in Islamic religious tradition, law and lore. This paper employed historical, sociological and ideological approaches to assess and appraise the common features of the Arabic works of the Arabic literati of Nigerian provenance, whose propensity for religiosity influenced their texts. The paper examined the predisposing factors as well as the extent of the religious influence. Of the factors identified, the most culpable are the symbiotic nexus between Arabic and Islam, influence of the literary heritage and religious revivalism of the 18th and 19th centuries in Hausaland as well as the influence of literary productions of the 'decadence’ era of Arabic literature. The paper identified and presented specific illustrations exhibiting the extent of proclivity for religiosity in the literary productions of Yoruba ‘Ulamā’. Findings from the study could serve as veritable pointers to the significance of the Arabic literary productions of the Arabic literati of Yoruba ancestry.